Cerebral microbleeds and CSF Alzheimer biomarkers in primary progressive aphasias. (20th March 2018) - Mendes, Aline; Bertrand, Anne; Lamari, Foudil; Colliot, Olivier; Routier, Alexandre; Godefroy, Olivier; Etcharry-Bouyx, Frédérique; Moreaud, Olivier; Pasquier, Florence; Couratier, Philippe; Bennys, Karim; Vercelletto, Martine; et al.
Abstract : Objective: To reveal the prevalence and localization of cerebral microbleeds (CMBs) in the 3 main variants of primary progressive aphasia (PPA) (logopenic, semantic, and nonfluent/agrammatic), to identify the relationship with underlying Alzheimer pathology, and to explore whether CMBs contribute to language breakdown. Methods: We used a cross-sectional design in a multicenter cohort of 82 patients with PPA and 19 similarly aged healthy controls. MRI allowed for rating CMBs (2-dimensional gradient recalled echo T2*, susceptibility weighted imaging sequences) and white matter hyperintensities. CSF Alzheimer disease biomarker analyses available in 63 of the 82 patients provided the stratification of PPA into subgroups with patients who had or did not have probable underlying Alzheimer pathology. Results: The prevalence of CMBs was higher in patients with PPA (28%) than in controls (16%). They were more prevalent in logopenic PPA (50%) than in semantic PPA (18%) and nonfluent/agrammatic PPA (17%). The localization of CMBs was mainly lobar (81%) with no difference between the PPA variants. CMBs were more frequent in PPA patients with positive than with negative CSF Alzheimer disease biomarkers (67% vs 20%). Patients with and without lobar CMBs had similar volumes of white matter hyperintensities. Language and general cognitive impairment in PPA was unrelated to CMB rates. Conclusions: CMB prevalence in PPA is higher than in healthy controls. CMBs were most prevalent in the logopenic variant, were related to underlying Alzheimer pathology, and did not affect the language/cognitive impairment. Our findings also suggest that CMB detection with MRI contributes to PPA variant diagnosis, especially of logopenic PPA, and provides an estimator of the underlying neuropathology.